Structure and chromosomal location of mouse and human CD52 genes. - Tone, M; Nolan, K; Walsh, L; Tone, Y; Thompson, SA; Waldmann, H (1999)
Human CD52 (CAMPATH-1 antigen) is an abundant surface molecule on lymphocytes and a favoured target for lymphoma therapy and immunosuppression. It comprises a small glycosylphosphatidylinositol (GPI) anchored peptide to which a large carbohydrate moiety is attached. Structurally similar proteins include the proposed mouse homologue, B7 antigen (B7-Ag; not to be confused with the CD28 ligand), and human and mouse CD24. Sequence similarities between CD52 and B7-Ag precursors are concentrated over the signal peptides and the sequences cleaved during GPI attachment. While the short mature peptides are not apparently homologous, the N-linked glycosylation site is retained in both. We describe similarities in exon-intron organisation, syntenic chromosome positions (human CD52, 1p36; mouse B7-Ag, chromosome 4, between Dsil and D4Nds16) and sequence homology in the promoter regions which strongly suggests that B7-Ag is the mouse homologue of CD52. The structure of these genes is also similar to that of mouse CD24, suggesting a common ancestor. Promoter activities and transcription start sites were also analysed. These results suggest that human CD52 and mouse B7-Ag gene expressions are controlled by TATA-less promoters.